Intrathecal Morphine in Postoperative Analgesia for Colorectal Cancer Surgery: A Retrospective Study. Issue 2 (8th November 2020) - Young, Jamie; Macpherson, Alistair; Thakerar, Arti; Alexander, Marliese
Abstract: Background: Colorectal cancer surgery is commonly performed with adequate analgesia essential for patient recovery. This study assessed the effectiveness of intrathecal morphine and patient-controlled analgesia (ITM + PCA) vs patient-controlled analgesia alone (PCA) for postoperative pain management in colorectal cancer surgery. Methods: This retrospective study extracted and analyzed data covering a 4-year period (2014–2018) from a clinical database with 24- and 48-hour postsurgery follow-up. Primary outcomes included pain scores, median opioid consumption (oral morphine equivalence dose), sedation, nausea and vomiting, and length of admission. Outcomes were analyzed for ITM + PCA vs PCA alone, overall and stratified by laparotomy or laparoscopy procedures. Results: In total, 283 patients were included: ITM + PCA (163) and PCA alone (120). Median opioid consumption in the first 24 hours for ITM + PCA vs PCA alone was lower for laparotomy (–32.7 mg, P <0.001) and laparoscopy (–14.3 mg, P <0.001). Median pain score (worst pain) within the first 24 hours for ITM + PCA vs PCA alone was similar for laparotomy ( P >0.05) and lower for laparoscopy (–1 unit, P =0.031). Sedation occurred less frequently for ITM + PCA vs PCA at 24 hours (3.5% vs 11.4%, P =0.031), with nonsignificant reduction at 48 hours (4.8% vs 18.8%, P =0.090) for laparotomy, but with no difference for laparoscopy ( P >0.05). Incidence of nausea and vomiting and length of admission were similar for ITM + PCA vs PCA alone for laparotomy or laparoscopy ( P >0.05). Conclusion: This retrospective study demonstrated that ITM + PCA can achieve similar analgesic effects after laparotomy and laparoscopy colorectal cancer surgery compared with PCA alone while resulting in a reduction of oral opioid consumption and lower incidence of sedation.